Corporate ESG Performance and Accounting Information Quality - Liu, Xinyang (Transactions on Economics, Business and Management Research, 2023)
This paper empirically examines the impact of ESG rating performance on the quality of corporate accounting information with 10015 listed companies in China's A-share market from 2012 to 2021. The results show that the better the ESG rating performance, the lower the level of real surplus management and the higher the quality of accounting information. Mechanism analysis shows that corporate ESG performance improves accounting information quality by reducing financing constraints and reducing information asymmetry. Heterogeneity analysis finds that the contribution of corporate ESG performance to accounting information quality is more significant in non-state-owned enterprises, non-polluting industry enterprises, enterprises in the eastern region. The research in this paper reveals the promotion effect of ESG on accounting information quality and provides a reference for the research on ESG in China.